Seeds: The Ecology of Regeneration in Plant Communities 2000
DOI: 10.1079/9780851994321.0111
|View full text |Cite
|
Sign up to set email alerts
|

Animals as seed dispersers.

Abstract: This chapter considers the process of seed acquisition by animals (or animal acquisition by seeds), the nature of seed treatment by the animals, animal mobility and seed deposition patterns, and finally the diversity of animals that disperse seeds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 0 publications
0
59
0
6
Order By: Relevance
“…They reported a higher removal of arillated seeds inside the forest whereas no difference was observed among intact and cleaned seeds placed on the edge of the forest. Beattie and Culver (STILES, 1992) reported that ants vary greatly in their response to different elaiosomes, and that variation is among species, populations and even within a population. According to Horvitz (1981) arils are similar to elaiosomes attracting ants since both are rich in lipids.…”
Section: Resultsmentioning
confidence: 99%
“…They reported a higher removal of arillated seeds inside the forest whereas no difference was observed among intact and cleaned seeds placed on the edge of the forest. Beattie and Culver (STILES, 1992) reported that ants vary greatly in their response to different elaiosomes, and that variation is among species, populations and even within a population. According to Horvitz (1981) arils are similar to elaiosomes attracting ants since both are rich in lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Bats.-In the New World, members of the Phyllonycterinae are known dispersing agents of the seeds of many plants (Pijl 1957;Janzen 1983a;Stiles 2000). There are however, no frugivorous bats at present native to the Joshua tree area (Hall 1981; Katherine Hinman pers.…”
Section: Mammaliochorymentioning
confidence: 99%
“…When available, all carnivores consume at least some juicy or fleshy fruits (Janzen and Wilson 1983) and Stiles (2000) considers them one of the major groups of fruit and seed-eating species of mammals (after primates and bats). There seems, however, to be no account of these animals eating the fruits of the Joshua tree, one reason being that at the time the fruits are ripe they are for the most part out of reach of the animals.…”
Section: Mammaliochorymentioning
confidence: 99%
“…Frugivorous birds are important components of ecosystems, as they influence plant regeneration through seed dispersal (Stiles 1992, Gorchov et al 1993, Pizo 1997, Howe & Miriti 2000, Bleher & Bohning-Gaese 2001. However, foraging behavior of birds may influence their effectiveness as dispersers (Sorensen 1984, Schupp 1993, Witmer & Van Soest 1998.…”
Section: Introductionmentioning
confidence: 99%